The Influence of Knowledge-Oriented Leadership on Enhancing Innovative Green Work Behavior with Green Work Engagement as A Mediator - Sri Winarni (Jurnal Manajemen Sains dan Organisasi, 2025)
Objective – This study investigates green HRM practices and knowledge-oriented leadership facilitating creative, green work in SMEs. This paper emphasizes the ways that sharing of leadership stimulates a green ideas climate. This type of leadership stimulates the sharing of knowledge, essential for green behavior, behaving as a coach encouraging the team with green and creative ideas. The emphasis here turns to "green work engagement" with the ways the employees relate to green practices such as recycling and energy conservation. Results indicate participative behavior contributes to green and creative work. Recent studies highlight the important role of knowledge-oriented leadership in building organizational trust and enhancing innovative behavior, especially in the green context Design/Methodology/Approach – examined this correlation. Data assisted with the analysis of the impact that the practices of HR and leadership styles have on green innovations and their outcomes from actual work experience. The method accredited the theoretical relationships utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) Findings –The study confirms the interconnectedness of KOL, GWE, and GIWB and supports the implementation of integrated management practices enhance employee engagement and encourage innovation in the environment of a green workplace. Conclusion and Implications – The research concludes that the integration of the sustainability policies of HR with the sharing of leadership styles significantly enhances green innovative work behavior. Green innovation flourishes through open communication, exchange of information, and facilitative regulations